Evaluasi Pelayanan Pemantauan Terapi Obat di Rumah Sakit X Tangerang - Febbyasi Megawaty; Shirly Kumala; Sesilia Andriani Keban (Fakultas Farmasi Universitas Pancasila, 2020)
Therapeutic Drug Monitoring (TDM) is a clinical practice to increase the effectiveness of therapy and minimize the risk of adverse drug reactions (ADR). The purpose of this study is to describe the implementation of TDM, and whether it is in accordance with the Regulation of the Minister of Health of the Republic of Indonesia (Permenkes) Number 72 of 2016 concerning pharmaceutical service standards at hospitals and the evaluation of TDM services conducted by pharmacists on inpatients. This research covers a descriptive study with a collection of retrospective data from TDM documents of inpatients during the period of January–May 2016 at X Hospital, Tangerang. The implementation of TDM by pharmacists based on the standards was 73%. The number of patients who met the inclusion criteria were 50 patients. Based on the diagnosis of the disease, patients with the potential of receiving TDM were patients with hypertension (10 patients; 20%), congestive heart failure (9 patients; 18%), and diabetes mellitus (8 patients; 16%). Whereas patients with both potential drug interaction and prescribed with more than 10 drugs was 29 patients (58%), patients with both potential drug interaction and diagnosed with three types of diseases was 19 patients (38%). The implementation of TDM in accordance with pharmaceutical service standards requires the competence of clinical pharmacist pharmacists with 2 years work experience. Potential drug interactions can be controlled by prioritizing TDM based on the number of drugs, complications of the disease and type of disease.